2001
DOI: 10.2135/cropsci2001.411218x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Puroindoline Grain Hardness Genotypes among Historically Significant North American Spring and Winter Wheats

Abstract: Grain hardness (“hard” or “soft” kernel texture) is the single most important trait in determining the utilization and marketing of wheat (Triticum aestivum L.). Puroindoline a and b proteins represent the molecular basis for this trait. This study surveyed the prevalence of puroindoline hardness mutations (alleles) among North American spring and winter wheat varieties with emphasis on those that are historically important. Each variety was assessed for kernel texture using the Single Kernel Characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
4
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 35 publications
8
105
4
2
Order By: Relevance
“…The situation may be more severe when polyploid plants are under abiotic stress, such as heat and drought during grain filling, which adversely affects endosperm development. Point mutations in Pinb can liberate the PIN proteins from binding to the starch granule surface and cause significant difference in grain texture Morris, 1997, 1998;Morris et al, 2001); however, the PIN proteins with the AAI activity remain in the endosperm cells. Therefore, deletion of Pina-Pinb genes provides the most efficient mechanism to reduce AAI activity and is the least detrimental because they are structural genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation may be more severe when polyploid plants are under abiotic stress, such as heat and drought during grain filling, which adversely affects endosperm development. Point mutations in Pinb can liberate the PIN proteins from binding to the starch granule surface and cause significant difference in grain texture Morris, 1997, 1998;Morris et al, 2001); however, the PIN proteins with the AAI activity remain in the endosperm cells. Therefore, deletion of Pina-Pinb genes provides the most efficient mechanism to reduce AAI activity and is the least detrimental because they are structural genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 40 T. aestivum accessions, 37 showed a conserved haplotype structure for Pina and Pinb in the D genome (Ha-D) and, as expected, a null haplotype for the A and B genomes. Of the 18 hard wheat cultivars that do not express the PINA protein (Morris et al, 2001), 'Red Egyptian', 'Sea Island', and 'Komar' showed the null haplotype at Ha-D. Further probing with BGGP and Gsp detected three copies in 'Sea Island' and 'Komar', but only two in 'Red Egyptian' (Fig. 4).…”
Section: Hexaploid Speciesmentioning
confidence: 99%
“…Numerous separate single nucleotide changes within Pina-D1 and Pinb-D1 (alleles Pinb-D1b, Pinb-D1c, etc.) result in high kernel hardness (Giroux et al 2000;Lillemo and Morris 2000;Morris et al 2001;Xia et al 2005;Chen et al 2006;Ram et al 2005). Grain softness proteins (GSPs) are closely related to puroindolines (Gautier et al 2000) and the grain softness protein-1 gene (Gsp-D1) is closely linked to the Ha locus in wheat (Jolly et al 1996) and T. monococcum L. (Gsp-Am1).…”
Section: Mots Clé S: Triticum Aestivum Durete´du Grain Puroindolinesmentioning
confidence: 99%
“…Based on these studies, at least 25 alleles at the Pinb-D1 locus have been reported (Lillemo and Morris 2000;Morris et al 2001;Tranquilli et al 2002;Ram et al 2005;Xia et al 2005;Chen et al 2006Chen et al , 2007Bhave and Morris 2008), but the Pinb-D1b allele is the most prevalent allele in US, Norwegian, Japanese, South Korean, Indian, and Chinese varieties (Chen et al 2006;Lillemo and Morris 2000;Morris et al 2001;Ikeda et al 2005;Ram et al 2005;Xia et al 2005). Unlike the Pinb-D1 locus, only a few mutations conferring kernel hardness have been reported at Pina-D1.…”
Section: Mots Clé S: Triticum Aestivum Durete´du Grain Puroindolinesmentioning
confidence: 99%
See 1 more Smart Citation